Respuesta :
Step-by-step explanation:
3(4x - 2) = 12x - 6
12x - 6 = 12x - 6
that is always true, no matter what value we pick for x.
so, this has infinite many solutions.
3(4x - 2) = -12x - 6
12x - 6 = -12x - 6
24x = 0
x = 0
this has one solution.
-3(4x - 2) = -12x - 2
-12x - 6 = -12x - 2
-6 = -2
this is never true, no matter what value we pick for x.
so, this has no solution at all.
Answer:
see below
Step-by-step explanation:
Hi!!
Here's how I found it:
First, I simplified all my equations.
1.12x-6=12x-6
2.12x-6=-12x-6
3.-12x+6=-12x-2
#1 has infinite solutions, given that the equations are identical to eachother. Any value of x will sufice.
#2 can be simplifed with algebra.
Cancel out the -6, since it is on both sides.
we are left with 12x=-12x, which can be solved with the value of 0. This has one solution.
#3 can also be simplifed using algebra.
Cancel out the -12x, since both sides have that.
you are left with:
6=-2
this will never have a solution, therefor, it is no solution.